Multiferrroics of (1 – x)BaFe12O19 – xBaTiO3 and (1 – x)CoFe2O4 – xPb(Zr0.53Ti0.47)O3 compositions with a template structure - Zhuravlev, Victor A. (Russian physics journal)
Magnetoelectric composites consisting of ferrimagnetic phases of barium hexaferrite and cobalt ferrite were prepared by the sol-gel combustion method, and ferroelectric powders BaTiO3 and Pb(Zr0.53Ti0.47)O3 were used as templates. The phase composition, magnetic and magnetoelectric characteristics of the obtained materials have been studied.